Arborinine from Glycosmis Pentaphylla (retz.) DC induces apoptosis through activation of Caspase-3/7 in human mammary gland Adenocarcinoma (MCF-7) cell line - Mohd Hussain, Nurlaili Najmie; Uzir, Bisha Fathamah; Mohd Hassan, Norazian (2016)
Arborinine is an acridone alkaloid found exclusively in Rutacae family has been shown to inhibit proliferation of a wide variety of cancer cell lines. The present study is aimed to isolate and investigate the anti-proliferative activity of arborinine, isolated from a Malaysian Rutaceae, G. pentapylla (Retz. D) on human mammary gland adenocarcinoma, MCF-7 cell line. Isolation and characterization of arborinine were conducted from the leaves of G.pentaphylla collected from Kelantan via acid-base extraction and wet column chromatographic techniques. The structure of arborinine was elucidated by comparing its spectroscopic data with published reports. Arborinine was studied for its anti-proliferative activity with the help of MTT assay and further with TUNEL and caspase-3/7 assay to investigate the apoptosis mechanism.